2015
DOI: 10.1002/cncr.29569
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer in China: The new frontier?

Abstract: Although the burden of lung cancer has started to decline in the United States in recent years, in China, the world's most populous nation, nearly 650,000 new cases are diagnosed each year. These staggering statistics call for urgent action at multiple levels of society to reduce the burden of lung cancer in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…NSCLC is typically diagnosed at an advanced stage, and the 5-year survival rate for lung cancer is approximately 15% (Henley et al, 2014). Current studies have shown that the prognosis of NSCLC can be attributed to a variety of environmental and genetic factors, such as TNM stage, therapy method, and genetic factors (Gou et al, 2015;Ramalingam and Khuri, 2015;Wei et al, 2015). Therefore, it is important to understand the role of various cancer-related genes in the development and prognosis of NSCLC, so as to identify the prognosis markers for NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…NSCLC is typically diagnosed at an advanced stage, and the 5-year survival rate for lung cancer is approximately 15% (Henley et al, 2014). Current studies have shown that the prognosis of NSCLC can be attributed to a variety of environmental and genetic factors, such as TNM stage, therapy method, and genetic factors (Gou et al, 2015;Ramalingam and Khuri, 2015;Wei et al, 2015). Therefore, it is important to understand the role of various cancer-related genes in the development and prognosis of NSCLC, so as to identify the prognosis markers for NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies showed that the prognosis of NSCLC was contributed to patients’ clinical status and genetic factors such as TNM staging, surgery, chemotherapy drugs, genetic heterogeneity including EGFR , KRAS , PIK3CA , ALK et al . 4, 5 . Chemotherapy is the main conventional and useful therapeutic method for advanced and metastatic tumors 6, 7 .…”
Section: Introductionmentioning
confidence: 99%